Apparent Metabolizable Energy of Corn and Rice Bran for Philippine Mallard Duck - Sean Vidad; Danilda Hufana Duran; Joice V. San Andres; Antonio J Barroga (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2022)
The metabolizable energy (ME) value of common feedstuffs for Philippine mallard duck (PMD) need to be established to formulate specific and balance diet for PMD. For this, the study was conducted to determine the apparent ME expressed in classical ME (AME) and nitrogen corrected ME (AMEn) of corn and rice bran for PMD. Eight PMD were used in the energy assay using the total collection method. An improvised digestibility cage was fabricated and used in the experiment modifying the basin technique in excreta collection. The homogenous wet mash of corn and rice bran were tube-fed to the PMD twice with an interval of six hours. Excreta collection was done for 54 hours from the last scheduled tube feeding. Feed and excreta samples were sent to UPLB for protein and gross energy analyses. The experiment was carried out using the Completely Randomized Design. The calculated AME and AMEn of corn and rice bran for PMD were 3.63 and 3.61 kcal/g and 1.97 and 1.95 kcal/g, respectively. Corn tends to have a higher ME value than rice bran. The ME value of corn and rice bran for PMD is greater than the data of PHILSAN, which is the reference standard for poultry and livestock nutrient requirements in the Philippines. The result show that corn and rice bran have higher energetic value for growing PMD than book values for poultry. PMD is efficient in utilizing the energy content of corn and rice bran as manifested by the higher ME value.